New Inhibitors in the Ageing Population: A Retrospective, Observational, Cohort Study of New Inhibitors in Older People with Hemophilia - Astermark, Jan; Ay, Cihan; Carvalho, Manuela; D'Oiron, Roseline; Moerloose, Philippe De; Dolan, Gerard; Fontana, Pierre; Hermans, Cedric; Holme, Pål Andre; Katsarou, Olga; Kenet, Gili; Klamroth, Robert; Mancuso, Maria Elisa; Marquardt, Natascha; Núñez, Ramiro; Pabinger, Ingrid; Tait, Robert; Valk, Paul van der (Thrombosis and Haemostasis, 2021)
Introduction A second peak of inhibitors has been reported in patients with severe hemophilia A (HA) aged >50 years in the United Kingdom. The reason for this suggested breakdown of tolerance in the aging population is unclear, as is the potential impact of regular exposure to the deficient factor by prophylaxis at higher age. No data on hemophilia B (HB) have ever been reported.Aim The ADVANCE Working Group investigated the incidence of late-onset inhibitors and the use of prophylaxis in patients with HA and HB aged ≥40 years.Methods A retrospective, observational, cohort, survey-based study of all patients aged ≥40 years with HA or HB treated at an ADVANCE hemophilia treatment center.Results Information on 3,095 people aged ≥40 years with HA or HB was collected. Of the 2,562 patients with severe HA, the majority (73% across all age groups) received prophylaxis. In patients with severe HA, the inhibitor incidence per 1,000 treatment years was 2.37 (age 40–49), 1.25 (age 50–59), and 1.45 (age 60 + ). Overall, the inhibitor incidence was greatest in those with moderate HA (5.77 [age 40–49], 6.59 [age 50–59], and 4.69 [age 60 + ]) and the majority of inhibitor cases were preceded by a potential immune system challenge. No inhibitors in patients with HB were reported.Conclusion Our data do not identify a second peak of inhibitor development in older patients with hemophilia. Prophylaxis may be beneficial in older patients with severe, and possibly moderate HA, to retain a tolerant state at a higher age.
Keywords: hemophilia A/B; inhibitors; prophylaxis; aging